2021
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_285_21
|View full text |Cite
|
Sign up to set email alerts
|

Quality of online news reporting of suicidal behavior in Myanmar

Abstract: Background: Media reporting of suicide has an essential role in the suicidal behavior of the general population. Aims: The aim of this study is to assess the quality of online news reports of suicidal behavior in Myanmar against the World Health Organization (WHO) reporting guidelines. Methods: We performed a content analysis of all available suicide-related news reports published in vernacular online newspapers of Myanmar. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The findings of this study correspond to the reviews that assessed the quality of media reporting of suicide in South‐East Asia 11,12 . The low adherence to WHO guidelines and sensational presentation of suicides have been consistently found in other Asian counties also 7,15–26 . One of the studies in India reported gender as the most common identity reported by the newspaper both in the title and main text 24 .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The findings of this study correspond to the reviews that assessed the quality of media reporting of suicide in South‐East Asia 11,12 . The low adherence to WHO guidelines and sensational presentation of suicides have been consistently found in other Asian counties also 7,15–26 . One of the studies in India reported gender as the most common identity reported by the newspaper both in the title and main text 24 .…”
Section: Discussionsupporting
confidence: 84%
“…[27][28][29] In contrast to potentially harmful characteristics, potentially helpful characteristics like providing hope to readers were less focused, which is comparable to the study findings from India, Bangladesh, Indonesia, Bhutan, Myanmar, and Thailand. 12,[15][16][17]30,31 Apart from rarely mentioning educative information on suicide prevention, suicide linkage with mental illness, substance abuse, warning signs, and other potentially helpful reporting characteristics encouraged in the WHO guideline were not identified. Nothing was mentioned about supportive helpline/hotline information for the people with suicidal thoughts, which is similar to the study findings from Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations